Dampak Moderasi Locus of Control terhadap Efektivitas Sistem Informasi Keuangan pada Kantor Kecamatan di Kota Semarang, Provinsi Jawa Tengah - Septiawati, Rohma; Astriani, Devi; Kiryanto, Kiryanto (Universitas Muhammadiyah Metro, 2021)
The purpose of this study was to analyze the impact of locus of control moderation, the factors that affect the financial information system at the sub-district office in the city of Semarang. This study's population was 16 Districts Offices in Semarang City and obtained 54 questionnaires, then analyzed moderating regression analysis (MRA). From the research results of the impact of Locus of Control Moderation on the Effectiveness of Financial Information Systems at the District Office in Semarang City, Central Java Province, the results of the research on the first hypothesis, the influence of top management on the effectiveness of information systems, are to examine the influence of user satisfaction on the effectiveness of information systems, to examine the influence of organizational culture on the effectiveness of information systems. The effectiveness of information systems, to examine the effect of locus of control on the relationship between top management on the effectiveness of information systems, to examine the effect of locus of control between user satisfaction on the effectiveness of information systems from the results of the research resulted that it has a positive and significant effect. Tujuan penelitian ini adalah untuk menganalisis pengaruh moderasi locus of control, faktor-faktor yang mempengaruhi sistem informasi keuangan pada kantor kecamatan di kota Semarang. Populasi penelitian ini adalah 16 Kantor Kecamatan di Kota Semarang dan diperoleh 54 kuesioner, kemudian dianalisis analisis regresi moderasi (MRA). Dari hasil penelitian pengaruh Locus of Control Moderation terhadap Efektifitas Sistem Informasi Keuangan pada Kantor Kecamatan Kota Semarang Provinsi Jawa Tengah diperoleh hasil penelitian hipotesis pertama yaitu pengaruh manajemen puncak terhadap efektivitas sistem informasi, untuk menguji pengaruh kepuasan pengguna terhadap efektivitas sistem informasi, untuk menguji pengaruh budaya organisasi terhadap efektivitas sistem informasi. Efektivitas sistem informasi, untuk menguji pengaruh locus of control terhadap hubungan antara manajemen puncak terhadap efektivitas sistem informasi, untuk menguji pengaruh locus of control antara kepuasan pengguna terhadap efektivitas sistem informasi dari hasil penelitian menghasilkan pengaruh yang positif dan signifikan